Frequency of subclinical peripheral neuropathy in cases of untreated brucellosis - Hilal Sanivar; Hatice Kose Ozlece; Nergiz Huseyinoglu; Emsal Aydin; Faik Ilik (Journal of Infection in Developing Countries)
Introduction: Brucellosis is a common zoonotic disease in some areas of the world. It may affect several organs and is known to involve the nervous system in 2.7–17.8% of affected patients. During the progression of brucellosis, peripheral neuropathies (PNs) have been reported. However, there are few studies investigating the presence of subclinical neuropathy in asymptomatic patients. In our study, we aimed to evaluate the presence of peripheral neuropathy using electrophysiological methods in newly-diagnosed untreated brucellosis patients.